“A Descriptive Study To Assess The Knowledge And Practice Regarding Ethical Aspects Of Pediatric Care Among Staff Nurses” - Rajan , Kavitha; Kumar Ray , Suresh (Journal of Neonatal Surgery, 2025)
BACKGROUND OF STUDY; The increasing complexity of ethical issues in pediatric healthcare necessitates enhanced competencies among staff nurses. Pediatric nursing is the specialty that providing nursing care of children and their families from birth through adolescence within the framework of normal physical, cognitive, and psychosocial development. It is not like other nursing specialty and should apply the accepted standards of practice, professional performance, and ethics. Pediatric nurses must examine their own values so they can provide nursing care in an ethical manner. AIM; To assess the knowledge and practice regarding ethical aspects of pediatric care among staff nurses”. MATERIALS AND METHODS: In this study, Quantitative approach and descriptive design is adopted to to assess the knowledge and practice regarding ethical aspects of pediatric care among staff nurses. The study is conducted in a selected private hospitals of different regions (Mumbai,Pune and Nashik) from Maharashtra state.180 samples were taken. Non-probability convenient sampling technique for selection of samples from the population of the study. A validated semi-structured questionnaire and observation check list assessed the staff nurses' knowledge and practices. Data were analysed using descriptive statistics and inferential statistics. RESULT: Knowledge assessment showed that most staff nurses had poor knowledge (87.2%). A smaller proportion demonstrated average knowledge (22, 12.2%). Only one nurse (0.6%) showed good knowledge, while none reached excellent knowledge. This indicates low baseline knowledge regarding ethical aspects of paediatric care. The practice levels showed that the majority of staff nurses had poor practice, (132, 73.3%). Average practice was noted (48, 26.7%) None of the nurses demonstrated good practice levels. This indicates that overall practice regarding paediatric care was largely inadequate across...